Applying business diagnostic method in companies certified by the quality management system ISO TS 16949 - Silva Boa Sorte Oliveira, Angela Alice [UNESP]; Da Silva, Messias Borges; Calado, Robisom Damasceno (Elsevier, 2013)
The aim of this work is to diagnose the maturity levels of companies certified by the ISO TS 16949:2009 Automotive Quality Management System and to determine whether they are considered World Class. The study method consists in a case study and uses an Industrial Benchmarking Questionnaire for gathering information related to practice and performance, through the Business Diagnostic Method (BDM). After identifying the maturity level of the analyzed companies, the Grey Relational Analysis will be used to identify the strengths and weaknesses of such companies, in order to provide subsidies for them to create improvement projects. © IFAC.